2006
DOI: 10.1128/aac.50.5.1875-1877.2006
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin and Clindamycin Resistance in Group B Streptococcal Clinical Isolates

Abstract: Erythromycin (EM) and clindamycin (CM) susceptibility testing was performed on 222 clinical isolates of group B Streptococcus. A multiplex PCR assay was used to detect the ermB, ermTR, and mefA/E antibiotic resistance genes. These results were compared to the phenotypes as determined by the standard EM/CM double disk diffusion assay.Group B Streptococcus (GBS) is one of the leading causes of neonatal bacterial infection. This type of infection commonly leads to pneumonia, septicemia, or meningitis. Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
60
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 15 publications
13
60
3
1
Order By: Relevance
“…In Belgium, as determined by the National Reference Centre for GBS, macrolide resistance increased from 10.4% in the early 2000s to 33% among invasive strains isolated from 2008 to 2011 [59]. These figures are consistent with similar reports from Europe [61][62][63][64][65], North America [60,[66][67][68][69][70], and Asia [71,72], except some surveillance studies in Sweden reported 510% [73], thus showing some geographical differences. Different mechanisms account for the acquired resistance to macrolides in streptococci [74].…”
Section: Gbs Clinically Relevant Antimicrobial Susceptibility Profilesupporting
confidence: 81%
“…In Belgium, as determined by the National Reference Centre for GBS, macrolide resistance increased from 10.4% in the early 2000s to 33% among invasive strains isolated from 2008 to 2011 [59]. These figures are consistent with similar reports from Europe [61][62][63][64][65], North America [60,[66][67][68][69][70], and Asia [71,72], except some surveillance studies in Sweden reported 510% [73], thus showing some geographical differences. Different mechanisms account for the acquired resistance to macrolides in streptococci [74].…”
Section: Gbs Clinically Relevant Antimicrobial Susceptibility Profilesupporting
confidence: 81%
“…For patients allergic to β-lactam antibiotics, macrolide antibiotics are used as alternatives. Gygax et al reported that resistance to macrolide antibiotics is an increasing problem for the treatment of GBS infections (20). In the present study, we found that all GBS strains were susceptible to penicillin, ceftriaxone, and cefepime, suggesting that penicillin should remain the first-line antibiotic for the treatment of GBS infection.…”
Section: Discussionsupporting
confidence: 62%
“…En los últimos años se ha reportado un aumento significativo de cepas de S. agalactiae resistentes a eritromicina y clindamicina, en diversas partes del mundo. En nuestra experiencia, en la Región Metropolitana de Santiago, luego de una década de pesquisa universal de S. agalactiae, en un hospital universitario, también se observó este aumento significativo de resistencia a macrólidos y lincosamida [14][15][16][17][18][19] . La vigilancia de resistencia antimicrobiana se hace indispensable para definir los fármacos de elección y alternativas, en un centro que aplique protocolos de prevención, como es el caso de Clínica Alemana Temuco.…”
Section: Esde Mediados De Los Años ´80unclassified